КЕҢЕС БАСЫЛЫМДАРЫНДАҒЫ ТҮРКИЯ МӘСЕЛЕЛЕРІ (Journal of history-rus, 2023)
The content of the article the publication in the Soviet press of the political and cultural relations of the Soviet government and the Turkish Republic is due to insufficient study of the chosen topic to date. In this regard, the article analyzes the cultural and political relations of the Soviet government and Turkey in the Soviet press, aimed at identifying the main reasons for the construction and development of mutual Soviet-Turkish relations. The leading approach to the study of this problem is the method of analyzing historical scientific and literary sources, with the help of which previous scientific articles published in Soviet periodicals of the history of Turkey of the Ataturk period were studied, and information on the research topic was collected from archival editions of the newspapers «Pravda» and «Izvestia» in published 1920-1938.The following methods were used in the study: the historical-genetic method, the historical-system method, the method of diachronic analysis, methods of synthesis and deduction, as well as the method of comparison. The results of the analysis carried out in the article comprehensively examines the cultural and political relations of the Soviet government and Turkey in the Soviet press, explains the rhetoric of Soviet newspapers from the point of view of the socialist regime, compares the news related to Turkey in the Soviet and Austrian, Hungarian and Afghan press, identifies the main reasons for the establishment and development of effective Soviet-Turkish relations of each of the parties, sound methodological conclusions are given and scientific conclusions are made on the these issues.